Pemberdayaan Remaja melalui Edukasi Kesehatan Reproduksi dan Pembentukan Edukator Sebaya untuk Pencegahan Kehamilan Tidak Diinginkan di Desa Ciburial Bandung - yuyunpratiwi; Risda Setianingsih; Siska Purbasari (Jurnal Pengabdian dan Ekspalanasi Nusantara, 2026)
Reproductive health issues among adolescents remain an important concern that can contribute to an increased risk of unintended pregnancy (UP), particularly due to limited knowledge and awareness regarding reproductive health. This community service program aimed to enhance adolescents’ knowledge, awareness, and active participation in preventing unintended pregnancy through reproductive health education and the establishment of peer educators in Ciburial Village, Bandung Regency. The program employed educational and participatory approaches involving 40 adolescents aged 13–19 years. Activities included reproductive health counseling, group discussions, peer educator training, as well as reproductive health mentoring and counseling services. Program evaluation was conducted using pre-test and post-test assessments to measure improvements in participants’ knowledge, complemented by observations of adolescent participation and engagement throughout the activities. The results demonstrated a significant increase in adolescents’ knowledge, as indicated by the improvement in the average score from 61.8 in the pre-test to 84.2 in the post-test. In addition, a Reproductive Health Youth Care Group (KRPKR) consisting of 10 adolescents was successfully established as peer educators. The program also enhanced adolescents’ awareness of the importance of maintaining reproductive health and preventing risky behaviors that may lead to unintended pregnancy. These findings indicate that community-based reproductive health education combined with a peer educator approach is effective in strengthening adolescents’ capacity and supporting the sustainability of reproductive health promotion at the village level.